2006
DOI: 10.1002/crat.200510648
|View full text |Cite
|
Sign up to set email alerts
|

Influence of La3+ ions on growth and NLO properties of KDP single crystals

Abstract: Single crystals of pure and Lanthanum added KDP crystals were grown from aqueous solution. The influence of La 3+ ions in KDP crystals is studied. Isolated centers are formed by La 3+ ions in KDP structure along (100) plane. La 3+ ions incorporated into superficial crystal growth layer and slightly affect the growth process as they generate weak lattice stresses. The creation of these weak lattice stress is confirmed by Vickers's micro hardness test. The HRXRD analysis showed reduced structural defects in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 16 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…The only difference is the reduction of peak intensity of Figure 6 (b) which is mainly due to the fact that the specimen doped with CH 3 COOK is considerably lesser than that of specimen doped with K 3 C 6 H 5 O 7 . Our previous work reported that the FWHM of pure KDP crystal is 22 arc s [7]. From the figure 6, one can conclude that the crystalline quality of KDP crystal is improved by the addition of either K 3 C 6 H 5 O 7 or CH 3 COOK.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The only difference is the reduction of peak intensity of Figure 6 (b) which is mainly due to the fact that the specimen doped with CH 3 COOK is considerably lesser than that of specimen doped with K 3 C 6 H 5 O 7 . Our previous work reported that the FWHM of pure KDP crystal is 22 arc s [7]. From the figure 6, one can conclude that the crystalline quality of KDP crystal is improved by the addition of either K 3 C 6 H 5 O 7 or CH 3 COOK.…”
Section: Resultsmentioning
confidence: 76%
“…The addition of the dopants in the optimum HRXRD analysis Crystalline perfection has a strong influence on the efficiency of the physical properties of crystals [30]. Recently a lot of works reported that the changes in the crystalline perfection of KDP and ADP crystals by the effect of additives can analyzed by the high resolution XRD characterization technique [7,31,32]. A multicrystal X-ray diffractometer designed and developed at National Physical Laboratory, New Delhi [33] has been used to study the crystalline perfection of the single crystal(s).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This material attracts the many researchers probably because of their simple structure and many desirable properties associated with a hydrogen bond system involving a large isotopic effect, broad transparency range, high laser damage threshold and relatively low production cost [1,2].…”
Section: Introductionmentioning
confidence: 99%